Neurocognition in childhood epilepsy: Impact on mortality and complete seizure remission 50 years later - Matti Sillanpää; Maiju M. Saarinen; Mira Karrasch; Dieter Schmidt; Bruce P. Hermann (Wiley, 2022)
Objective
To study associations of the severity of impairment in childhood neurocognition (NC) with long-term mortality and complete seizure remission.
Methods
A population-based cohort of 245 subjects with childhood onset epilepsy was followed up for 50 years (median = 45, range = 2-50). Childhood NC before age 18 years was assessed as a combination of formal intelligence quotient scores and functional criteria (school achievement, working history, and psychoneurological development). Impaired NC was categorized with respect to definitions of intellectual functioning in International Classification of Diseases, 10th revision (R41.83, F70-F73). The outcome variables, defined as all-cause mortality and 10-year terminal remission with the 5 past years off medication (10YTR), were analyzed with Cox regression models.
Results
Of the 245 subjects, 119 (49%) had normal childhood NC, whereas 126 (51%) had various degrees of neurocognitive impairment. During the 50-year observation period, 71 (29%) of the subjects died, 13% of those with normal and 44% of those with impaired NC. The hazard of death increased gradually in line with more impaired cognition, reaching significance in moderate, severe, and profound impairment versus normal NC (hazard ratio [Bonferroni corrected 95% confidence interval] = 3.3 [1.2-9.2], 4.2 [1.2-14.2], and 5.5 [2.4-12.3], respectively). The chance for 10YTR was highest among subjects with normal NC (61%), whereas none of those with profound impairment reached 10YTR. In the intermediate categories, the chance was, however, not directly related to the increasing severity of impairment.
Significance
The severity of neurocognitive impairment during childhood shows a parallel increase in the risk of death. In comparison with normal NC, subjects with lower childhood NC are less likely to enter seizure remission. However, normal NC does not guarantee complete remission or prevent premature death in some individuals with childhood onset epilepsy.